Potentiometric Studies of Complex Formation between Ce(III) and 3-Chloro-2-hydroxy Acetophenone - Palaskar, N.G.; Ubale, Sanjay; Farooqui, Mazhar; Ubale, Milind; Kotharkar, Sandeep (Asian Journal of Chemistry, 2010)
Stability constants of binary complex of Ce(III) with 3-chloro- 2-hydroxy acetophenone at different temperature and in different ratio of water to dioxane has been determined. The thermodynamic parameters ΔH, ΔG and ΔS values are reported.